Reconnecting Fire Culture of Aboriginal Communities with Contemporary Wildfire Risk Management - Amos Atkinson; Cristina Montiel-Molina (Fire, 2023)
This paper aims to provide a better understanding of the transition towards a new paradigm of wildfire risk management in Victoria that incorporates Aboriginal fire knowledge. We show the suitability of cultural burning in the transformed landscapes, and the challenges associated with its reintroduction for land management and bushfire risk reduction after the traumatic disruption of invasion and colonization. Methods of Environmental History and Regional Geography were combined with Traditional Ecological Knowledge to unravel the connections between past, present and future fire and land management practices. Our study area consists of Dja Dja Wurrung and Bangarang/Yorta Yorta Country in north-central Victoria. The results show (i) the ongoing socio-political process for building a renewed integrated fire and land management approach including cultural burning, and (ii) the opportunities of Aboriginal fire culture for restoring landscape resilience to wildfires. We conclude that both wildfire risk management and cultural burning need to change together to adapt to the new environmental context and collaborate for mutual and common benefit.